Genetic variability of Hedysarum coronarium L. using molecular markers - Trifi-Farah N.; Marrakchi M. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The study of genetic diversity in Hedysarum coronarium L. has been performed by the help of RFLP analysis in 75 individuals representing five local populations from various geographical origins. Taking advantages of the large variation shown by the ribosomal RNA genes, we were interested in the use of nuclear ribosomal genes as RFLP markers to analyse the genetic variation among and within several spontaneous populations of H. coronarium. A homologous rDNA probe was used for southern hybridization to generate patterns from five spontaneous populations. The distribution of the generated polymorphic bands was studied using a multivariate analysis. It has been assumed that a high degree of rDNA polymorphism was observed. On the other hand, the geographical origin was not a determinant criterion for population clustering. In addition, a considerable genetic diversity has been detected in the case of populations characterized by a maximum of phenotypic variability (opposite geotropism). Our data are in good agreement with results based on isozyme markers.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)